Plasma genotyping for EGFR T790M in non-small cell lung cancer: ready for clinical practice? - Bersanelli, Melissa; Gelsomino, Francesco; Buti, Sebastiano; Fiorentino, Michelangelo; Tiseo, Marcello (Translational Cancer Research, 2017)
The outstanding article recently published in the Journal of Clinical Oncology by Oxnard and coauthors, about plasma genotyping in advanced non-small cell lung cancer (NSCLC) patients treated with osimertinib in the AURA phase I trial (1), represents an important further step towards the validation of the liquid biopsy in all possible settings and offers the cue for some careful reflections.